PELATIHAN KEMAMPUAN BERHITUNG DAN MEMBACA BAHASA INGGRIS DENGAN MENGGUNAKAN PERMAINAN EDUKATIF WORDWALL - Syifa Alfina Nugraha, Siti Nurmalihah, Ahmad Ramdan Nurfaiz, Linda (JURNAL PENGABDIAN KEPADA MASYARAKAT SERUMPUN MENGABDI, 2025)
This training aims to measure the effectiveness of using Wordwall educational games in improving English counting and reading skills in elementary school students. The research method used was a pseudo-experiment with a pretest-posttest design. The research subjects were grade 5 students at SDN Kadudodol 2. Data were collected through counting and reading skill tests before and after the application of Wordwall game for 1 day. The results of data analysis showed a significant increase in students' counting and reading skills after the training. This shows that Wordwall game can be an interesting and effective alternative in learning math and English.